Pump Switching-Induced Transients in Water Distribution Networks—Preliminary Laboratory Experiments - Caterina Capponi; Debora Falocci; Bruno Brunone; Yu Xiaodong; Yu Chao; Silvia Meniconi (Engineering Proceedings)
The Water Engineering Laboratory (WEL) of the University of Perugia hosts a real-scale water distribution network (WDN) with a service line comprising high-density polyethylene (HPDE) pipes and supplied by two pumps in series. The carried out unsteady-state tests show the WDN behavior during transients due to pump switching-on and -off. In particular, they underline the most pressure-stressed sections of the system. The obtained results can help water utility managers in protecting these sections with the aim to preserve the integrity of the WDN.